Piezomorphic Materials. Issue 3 (20th June 2012) - Alderson, Andrew; Alderson, Kim L.; McDonald, Samuel A.; Mottershead, Beth; Nazare, Shonali; Withers, Philip J.; Yao, Yong T.
Abstract The development of stress‐induced morphing materials called piezomorphic materials is reported. The preparation of a piezomorphic material is achieved by introducing spatial dependency into the compliance matrix describing the elastic response of a material capable of undergoing large strain deformation. In other words, it is necessary to produce an elastic‐gradient material. This is achieved through modification of the microstructure of the compliant material to display gradient topology. Examples of polymeric (PU) foam and microporous polymer (ex‐PTFE) piezomorphic materials are presented. These materials open up new morphing applications where dramatic shape changes can be triggered by mechanical stress.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>